Solve the following difference equation "\\Delta\\lambda^k=-k+5; \\lambda^6=0"
Solution
Rewrite the equation in factorial powers;
∆"\\lambda^k" =-k(1)+5
Apply the anti-difference operator ∆-1 as;
∆-1k(n)="\\frac{1}{(n+1)}" kn+1+c
Which gives ;
"\\lambda^k" =-("\\frac 12" )k(2)+5k(1)+c
Now we apply the given condition;"\\lambda^6"=0
0=-("\\frac12")62+5(6)+c
c=-12
So that;
"\\lambda^k"=-("\\frac12")k(2)+5k(1)-12
Convert the equation to ordinary powers of k;
We know,k(1)=k and k(2)=-k+k2
Replace in the equation;
"\\lambda^k" =-"\\frac12"(-k+k2)+5k-12
Simply;
Answer
"\\lambda^k" =-"\\frac12"k2+"\\frac{11}2"k-12
Comments
Leave a comment